Qi Gong Wan ameliorates adipocyte hypertrophy and inflammation in adipose tissue in a PCOS mouse model through the Nrf2/HO-1/Cyp1b1 pathway: Integrating network pharmacology and experimental validation in vivo. (30th January 2023) - Zheng, Ruqun; Shen, Haoran; Li, Jie; Zhao, Jiansen; Lu, Lingjing; Hu, Mianhao; Lin, Zixin; Ma, Hongxia; Tan, Huiyan; Hu, Min; Li, Juan
Abstract: Ethnopharmacological relevance: Initially recorded in Yifang Jijie (an ancient Chinese text), Qi Gong Wan (QGW) is used to treat obese women with infertility. QGW can help promote follicular development and maturation, regulate the balance of serum hormones between testosterone and estradiol, enhance endometrial receptivity, improve waist circumference, and ameliorate insulin resistance. It contains eight herbs: Pinellia ternata (Thunb.) Makino (Banxia), Citrus maxima (Burm.) (Juhong), Poria cocos (Schw.) Wolf. (Fuling), Atractylodes macrocephala Koidz (Baizhu), Cyperus rotundus L. (Xiangfu), Conioselinum anthriscoides 'Chuanxiong' (Chuanxiong), Massa Medicata Fermentata (Shenqu), and Glycyrrhiza uralensis Fisch. ex DC. (Gancao). However, the underlying mechanism of how QGW affects women with PCOS remains unclear. Aim of the study: QGW has been widely used to treat PCOS patients with obesity clinically. This study was designed to identify its chemical and pharmacological properties. Materials and methods: Network pharmacology was used to predict the active compounds, potential targets, and pathways of QGW. Female C57BL/6J mice were injected with letrozole and fed a high-fat diet to establish a PCOS-insulin resistance (PCOS-IR) model. Body weight, estrous cycles, ovarian pathology, and serum insulin resistance were measured. qRT-PCR was used to examine the inflammation-related and steroid hormone biosynthesis-related mRNA expression in adipose tissue. Western blotting was used to determine the protein levels of Nrf2, HO-1, and Cyp1b1 in adipose tissue. Molecular docking was used to reveal the key chemical compounds of QGW. Results: Network pharmacology revealed a total of 91 active ingredients in QGW that were associated with 167 targets. QGW could potentially treat PCOS-IR via nitrogen metabolism, steroid hormone biosynthesis, and ovarian steroidogenesis pathways. In the PCOS-IR mouse model, we found that QGW decreased the mean diameter of adipocytes and the total adipocyte area. Furthermore, QGW was found to significantly lower the expression of inflammation-related genes including Tnfɑ and C4a/b and the steroid hormone biosynthesis-related gene Cyp1b1 . QGW showed a tendency to improve cystic follicles, fasting insulin, and HOMA-IR index in the PCOS-IR mouse model. Combining these findings with the results of KEGG analysis, we conclude that QGW promotes the Nrf2/HO-1/Cyp1b1 pathway to protect adipose tissue under conditions of PCOS. Molecular docking revealed that rutin, nicotiflorin, and baicalein may be the key chemical compounds of QGW through which it improves adipocyte hypertrophy and inflammation. Conclusions: QGW improved adipocyte hypertrophy and inflammation in the PCOS-IR mouse model by activating the Nrf2/HO-1/Cyp1b1 pathway to protect adipose tissue. Our work thus provides a new research avenue for the study of traditional Chinese medicine in the treatment of PCOS. Graphical abstract: Image 1 Highlights: The mechanisms of QGW were predicted by network pharmacology. QGW favorably ameliorated adipocyte hypertrophy and inflammation in the PCOS-IR mouse model by activating the Nrf2/HO-1/Cyp1b1 pathway. Rutin, nicotiflorin, and baicalein may be the key chemical compounds of QGW through which it improves adipocyte hypertrophy and inflammation.